GEOTECNOLOGIAS APLICADAS AO ESTUDO COMPORTAMENTAL DAS ILHAS DE CALOR URBANAS - Costa, Gizely Azevedo (2020)
The urbanization process can alter the physical space and influence the environmental quality to the detriment of the reduction of green areas present in large urban centers. As a consequence, many cities are impacted by the effect of heat islands, a phen